2015
DOI: 10.1186/s12889-015-1913-0
|View full text |Cite
|
Sign up to set email alerts
|

Cross-sectional community-based study of the socio-demographic factors associated with the prevalence of dengue in the eastern part of Sudan in 2011

Abstract: BackgroundDengue is caused by an arthropod-borne flavivirus. Infection can be either primary or secondary based on serology, with each stage of the disease characterized by specific serological conversion and antibody formation. Further study is needed to fully identify the factors associated with and predisposing to dengue infection. The objective of this study was to identify socio-demographic factors associated with the prevalence of dengue serotypes in Kassala State in the eastern part of Sudan in 2011.Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
41
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 25 publications
2
41
3
Order By: Relevance
“…The PCR reveals negative results. Although not all these viruses were responsible for VHF, we screening these viruses due to many studies were conducted in eastern Sudan revealed the presence of highly seropositive of dengue and HEV [33,[43][44][45]. Thirteen patients were positive for dengue IgM in ELISA, although the PCR results for all DFV types were negative, which may be explained by the presence of several genetically and antigenically different serotypes of the DFV worldwide [6,7,43,[46][47][48].…”
Section: Discussionmentioning
confidence: 98%
“…The PCR reveals negative results. Although not all these viruses were responsible for VHF, we screening these viruses due to many studies were conducted in eastern Sudan revealed the presence of highly seropositive of dengue and HEV [33,[43][44][45]. Thirteen patients were positive for dengue IgM in ELISA, although the PCR results for all DFV types were negative, which may be explained by the presence of several genetically and antigenically different serotypes of the DFV worldwide [6,7,43,[46][47][48].…”
Section: Discussionmentioning
confidence: 98%
“…The high incidence of the disease has become of great concern to the public health officers worldwide [7][8][9]. In the recent years, DENV has spread all over the Sudan resulting in frequent occurrence of sporadic cases and multiple outbreaks [10][11][12][13]. The major economic losses caused by DENV infections in Sudan are almost exclusively confind to the Kassala state, eastern Sudan [10,11,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%
“…Another important factor in the transmission of dengue infection in this study was persons-per-room, which indirectly measures host density or overcrowding. The reason lies behind the behavior of the dengue vector, which feeds on several individuals in a given time 2 , therefore increasing the risk of transmission of dengue virus to several individuals in households with a higher number of persons per room 13 . Overcrowding is always associated with poverty and lower socioeconomic status, making it an important social predictor of dengue infection 14 .…”
mentioning
confidence: 99%